Case for More Autologous Transplants in Myeloma in Resource-Constrained Settings - Singh, Suvir; Sharma, Rintu (Indian Journal of Medical and Paediatric Oncology, 2022)
Multiple myeloma is characterized by a near universal risk of relapse. Autologous stem cell transplantation provides a significant progression free survival benefit but is under utilized worldwide. We provide a small snapshot of why ASCT assumes greater importance in resource-constrained settings.
Keywords: hematology; medical oncology; myeloma; transplant